The intersection of obesity and (long) COVID-19: Hypoxia, thrombotic inflammation, and vascular endothelial injury - Xiang, Mengqi; Wu, Xiaoming; Jing, Haijiao; Novakovic, Valerie A.; Shi, Jialan (Frontiers in Cardiovascular Medicine, 2023)
The role of hypoxia, vascular endothelial injury, and thrombotic inflammation in worsening COVID-19 symptoms has been generally recognized. Damaged vascular endothelium is a crucial cofactor in forming in situ thrombosis and is also involved in the occurrence of pulmonary dysfunction and hypoxemia. Hypoxemia and thrombosis can also reinforce mutually. Obesity, an independent risk factor for severe respiratory diseases, contributes to high rates of mechanical ventilation and mortality in COVID-19 patients. In obese people, during the acute period of COVID-19, the accumulation of fat restricts the alveolar expansion; chronic low-grade inflammation aggravates tissue damage and inflammation diffusion; vascular endothelium has a vulnerable basis leading to early injury and pre-thrombotic state; enhanced procoagulant activity and microthrombus promote early vascular perfusion obstruction. Obesity also increases the risk of sequelae after discharge from hospital. Persistent viral presence, long-term inflammation, microclots, and hypoxia may all be involved in the development of persistent symptoms, suggesting the possibility to explore the particularity of long COVID in obese patients. Early interventions, including supplemental oxygen, comprehensive antithrombotic therapy, anti-inflammatory drugs, and other means show effectiveness in many studies and are recommended to use, which can prevent serious hypoxia, thromboembolic events, and systemic inflammation to reduce intensive care unit admission, mortality, and sequelae.